2021
DOI: 10.1093/eurheartj/ehab724.1425
|View full text |Cite
|
Sign up to set email alerts
|

GPVI inhibition by glenzocimab synergistically inhibits atherosclerotic plaque-induced platelet activation when combined with conventional dual antiplatelet therapy

Abstract: Introduction Aspirin and a potent platelet P2Y12 inhibitor, such as prasugrel or ticagrelor, are not always sufficient to prevent thrombus formation in patients with ST-elevation MI (STEMI), leading to “slow flow” or “no reflow” effects after stenting. GPIIb/IIIa inhibitors, such as eptifibatide, may help in this setting, but are not used routinely due to their bleeding risk. GPVI has critical roles in thrombosis and a minimal role in haemostasis. Here we tested whether depletion of GPVI has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Platelet activation markers, particularly the highly GPVI‐dependent PS exposure, 40–42 were also markedly decreased on both surfaces with Nb2 treatment. This is similar to that seen with the anti‐GPVI F(ab)' fragment of mAb 9O12, 8 the precursor antibody to the humanized form ACT017 (Glenzocimab) 43 . Combined inhibition of the two main platelet integrins α2β1 and αIIbβ3 was required to produce similarly strong inhibition of thrombus formation and platelet activation, but lacked the effect on procoagulant platelet formation achieved by Nb2.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Platelet activation markers, particularly the highly GPVI‐dependent PS exposure, 40–42 were also markedly decreased on both surfaces with Nb2 treatment. This is similar to that seen with the anti‐GPVI F(ab)' fragment of mAb 9O12, 8 the precursor antibody to the humanized form ACT017 (Glenzocimab) 43 . Combined inhibition of the two main platelet integrins α2β1 and αIIbβ3 was required to produce similarly strong inhibition of thrombus formation and platelet activation, but lacked the effect on procoagulant platelet formation achieved by Nb2.…”
Section: Discussionsupporting
confidence: 65%
“…This is similar to that seen with the anti‐GPVI F(ab)' fragment of mAb 9O12, 8 the precursor antibody to the humanized form ACT017 (Glenzocimab). 43 Combined inhibition of the two main platelet integrins α2β1 and αIIbβ3 was required to produce similarly strong inhibition of thrombus formation and platelet activation, but lacked the effect on procoagulant platelet formation achieved by Nb2. As eptifibatide treatment causes excessive bleeding, 44 combined inhibition of αIIbβ3 and α2β1 would not be a viable treatment strategy to prevent thrombus formation.…”
Section: Discussionmentioning
confidence: 98%
“…31 In vitro studies have indicated that 9O12-Fab, as well as its derivative ACT017, suppresses collagen-and fibrin-induced platelet aggregation and thrombus formation under flow. 17,32,33 Importantly, the 9O12-Fab was found to interfere with all GPVI-induced platelet responses, including the surface expression of P-selectin and phosphatidylserine. 32 A similar suppression of collagen-induced platelet activation can be achieved by targeting the protein tyrosine kinase cascade downstream of GPVI, e.g., utilizing the Syk-kinase inhibitor PRT-060318.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, targeted drug delivery using exosomes has been developed especially in drug delivery to tumor cells and heart tissues. Tumor cells can change their microenvironment by using exosome communication between cells and the immune system [12][13][14][15]. Acquired exosomes from liquid biopsies are not invasive and therefore have potential for the development of genomic and proteomic research for disease diagnosis and prognosis monitoring.…”
Section: Introductionmentioning
confidence: 99%